Study on Steel Content Estimation of Reinforced Concrete Rectangular Pool Wall - Yanfang Li; Yonghua Wang; Chao Ren; Bo Zhang; Hongzhen Kang (Discrete Dynamics in Nature and Society)
For water purification plants and sewage treatment plants, there is no reference optimal steel content for the wall of reinforced concrete water pool. Focusing on the reinforced concrete water pool, this paper explores the optimal wall thickness and optimal reinforcement area at different bending moments and identifies the optimal steel content. To solve the problem, the authors established the discrete distribution function for the engineering cost per unit length of pool wall and steel content. The theoretical model was verified by numerous data through Excel numerical simulation. The research results provide a reference optimal steel content for designers and help to save the engineering cost of pool wall.